IMPLEMENTASI METODE PEMBELAJARAN FASTER IS BETTER BERBASIS PEER TEACHING SEBAGAI UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI IPS SMA NEGERI 9 YOGYAKARTA - Pranesti, Arin; Hidayah, Nurul; Latri, Sekar (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractThis study aims to increase the learning motivation through the implementationof peer teaching-based faster is better learning method in State Senior HighSchool 9 Yogyakarta. The method used in this study is classroom action researchdeveloped by Kemmis and Taggart. The subjects of this study are 21 students of gradeXI of Social Science of SMAN 9 in Yogyakarta. The object of this study, learningmotivation, is expected to increase through the implementation of the peer teachinglearning method. The data were collected by using questionnaires and field notes. Theresults show that in the first cycle of the research,the motivation of most students was(64.99%). Based on the observations, in the second cycle the students’ motivation hasincreased by 1.19% to reach 66.18% in the second cycle.